An Analysis Of The Third Language Acquisition To A Five-Year-Old Girl In Terms Of Vocabulary - Ida Nur Saputri; Widyashanti Kunthara Anindita (Universitas Musamus Merauke, 2022)
Language is a way to communicate since we were born, especially for children since they were born they need to communicate what they want to the people around them. Growing and knowing many languages make them has a process of acquiring their language. In this research, the researcher wrote the observation about how a five-year-old girl acquires English words in terms of vocabulary and what kinds of English vocabulary that she acquires every day. The utterances of a five-year-old girl named Tsaqifa who is living in non-speaking English community are the data of the research. In this research, the writer is going to tell Psycholinguistics of a five-year-old girl in terms of vocabulary. This research used descriptive qualitative research method. To collect the data, the researcher used observation method and taking note method with the help of recording on the researcher’s phone. This research used observation to analyze the data by using referential identity method. The researcher found out the first about kinds of vocabularies that she acquire such as Noun 66%, Adjective 22%, Adverb 1%, Exclamation 1%, and Verb 10%. Second, on how a five-year-old girl acquires her language in terms of vocabulary such as Imitating, Watching, Listening English songs and Learning English from school.